2012
DOI: 10.1371/journal.pone.0042564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD166 as a Surface Marker for Enriching Prostate Stem/Progenitor and Cancer Initiating Cells

Abstract: New therapies for late stage and castration resistant prostate cancer (CRPC) depend on defining unique properties and pathways of cell sub-populations capable of sustaining the net growth of the cancer. One of the best enrichment schemes for isolating the putative stem/progenitor cell from the murine prostate gland is Lin-;Sca1+;CD49fhi (LSChi), which results in a more than 10-fold enrichment for in vitro sphere-forming activity. We have shown previously that the LSChi subpopulation is both necessary and suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 58 publications
4
74
0
2
Order By: Relevance
“…Previous studies showed that androgen receptor expression in cells overexpressing S100P increased significantly, and that there is a close relationship between androgen receptors and cell proliferation (Lee et al, 2011). Accordingly, Jiao et al (2012) found that S100P expression promoted prostate cancer progression both in vitro and in vivo. Our study showed that the S100P expression positive rate in patients with distant metastasis was 4.00%, significantly lower than that of patients without metastasis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies showed that androgen receptor expression in cells overexpressing S100P increased significantly, and that there is a close relationship between androgen receptors and cell proliferation (Lee et al, 2011). Accordingly, Jiao et al (2012) found that S100P expression promoted prostate cancer progression both in vitro and in vivo. Our study showed that the S100P expression positive rate in patients with distant metastasis was 4.00%, significantly lower than that of patients without metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…It has a very important role in maintaining the self-renewal and pluripotency ability of embryonic stem cells. Several studies have found that OCT4 expression in the healthy population is low, whereas OCT4 expression is high in gallbladder carcinoma, pancreatic cancer, and liver cancer (Wang et al, 2012). Specially, its expression level is upregulated following clinical upstaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although castration-resistant PCSCs have not yet been uncovered in primary human PCa samples, recent studies have provided hints that some PCSC subpopulations may express low levels of AR and intrinsically be resistant to castration. 8,11,55,99 It is conceivable that the expansion of such cells may promote CRPC development. As a result, these castration-resistant PCa cells may represent potential cellular targets for novel drug development.…”
Section: Cell Of Origin For Pca and Pcscsmentioning
confidence: 99%
“…53 Moreover, cancer cells expressing a luminal phenotype can regenerate new tumors after androgen replacement, 53 suggesting that SC-like cancer cells with the luminal progenitor phenotypes might be candidate cells of origin for CRPC. A cell surface marker, CD166, is found to be highly expressed in human CRPC samples, and, importantly, LSC hi CD166 hi cells in the Pten-null model have much enhanced sphere-formation abilities compared with the other subpopulations, 55 suggesting that the CD166 hi cell population may be enriched in castrationresistant PCSCs. Work from our lab indicates that PSA −/lo PCa cells are more clonal and clonogenic than the corresponding bulk PSA + PCa cells in androgen-deficient conditions in vitro and are more tumorigenic than PSA + cells in fully castrated mice.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…218,219 In various tumors, cancer stem cells can be identified by high membrane expression of CD166. 220,221 These studies show that CD166 regulates self-renewal in HSCs and tumor cells, and its expression in the endosteal niche and HSPCs is essential for proper hematopoiesis.…”
mentioning
confidence: 99%